Raw Material Inventory Control on Probabilistic Demand and Lead Time Using Continuous Review System - Ali Parkhan; Imam Djati Widodo; Erlangga Fausa; Qurtubi (Journal of Industrial Engineering and Halal Industries, 2023)
Excess inventory will lead to high inventory costs caused, among others, by damage and possible loss of stored goods embedded capital; on the other hand, a list is needed to ensure fulfillment of needs and reduce demand fluctuations and supply fluctuations to avoid loss of profit opportunities. This study aims to manage the uncertainty of usage and lead time in a wooden toy company, which can result in an excess or shortage of raw materials in the inventory system. It is necessary to control inventory to ensure optimal inventory; that is, needs can be met with minimal inventory costs and adequate service levels. The result, optimal condition is achieved if the company orders wood when the amount of inventory is (r) = 24,422 units with an order quantity of (Q) = 10,010 units each time you place an order, with a total inventory cost in 2023 of IDR 362,156,168, this policy will result in a service level (η) = 95.14%.